Minimizing Risks in Organ Transplantation: Notify Project New Developments. (July 2018) - Martinez-Cantullera, Aurora Navarro; Carella, Claudia; Petrisli, Evangelia; Strong, Michael D.; Noel, Luc; Ushiro-Lumb, Ines; Nalesnik, Michael; Shaw, Bronwen; Whitaker, Barbee; Muñiz-Diaz, Eduardo; Wiersum-Osselton, Jo; Ashford, Paul; et al.
Abstract : Introduction: Risks associated with organ transplantation are minimized through quality and safety guidelines and regulations. In the last 10 years, vigilance and surveillance (V&S) have been promoted through legislation and international initiatives to improve safety and quality. The Notify Project is the first global initiative to promote V&S and was initiated in 2010 under the World Health Organization (WHO) Resolution WHA 63.22 which recognizes the need for V&S of adverse occurrences in the therapeutic use of organs, tissues, blood and cells. The WHO and the Italian National Transplant Center (CNT) joined forces to create the Notify Project with the objective to support and improve V&S worldwide. Material and Methods: The Notify project has created a series of tools which include: an open-access library of published adverse occurrences including national and international vigilance reports and the publication of a V&S Booklet. Results: During 2017, the second edition of the Booklet included blood and updated all the topics including the most recent publications in the field. The Booklet contains information about all types of Medical Products of Human Origin (MPHO) and V&S aspects. The topics developed in the Booklet incorporate the history and general V&S overview; aspects on global governance of MPHO; organization and key factors for an effective V&S system; responsibilities; clinical practice surveillance; quality management; risks associated for every MPHO; triggers for a national adverse occurrence notification; review of the most common transmissible diseases, protocols for its investigation and tools for learning from errors. Conclusions: The Notify Project was established to create awareness of V&S worldwide by disseminating a variety of tools. The Library is constantly updated with documented didactic cases of adverse occurrences arising with the clinical application of MPHO. In 2017, the Project has published a new edition of the Notify Booklet, which includes blood, and has the aim to become a unique reference guide for regulators, competent authorities and professionals to develop a well structured, organized and efficient V&S system. International experts from multidisciplinary backgrounds produced this second edition, to ensure the quality and reliability of the Library's Booklet. The Booklet promotes the involvement of health professionals, competent authorities and scientific societies working on V&S across the globe.